Fabrication of UO2 Porous Pellets on a Scale of 30 kg-U/Batch at the PRIDE Facility - Sang-Chae Jeon; Jae-Won Lee; Ju-Ho Lee; Sang-Jun Kang; Kwang-Yun Lee; Yung-Zun Cho; Do-Hee Ahn; Kee-Chan Song (Advances in Materials Science and Engineering, 2015)
In the pyroprocess integrated inactive demonstration (PRIDE) facility at the Korea Atomic Energy Research Institute (KAERI), UO2 porous pellets were fabricated as a feed material for electrolytic reduction on an engineering scale of 30 kg-U/batch. To increase the batch size, we designed and modified the corresponding equipment for unit processes based on ceramic processing. In the course of pellet fabrication, the correlation between the green density and sintered density was investigated within a compaction pressure range of 106–206 MPa, in terms of the optimization of processing parameters. Analysis of the microstructures of the produced UO2 porous pellets suggested that the pellets were suitable for feed material in the subsequent electrolytic reduction process in pyroprocessing. This research puts forth modifications to the process and equipment to allow the safe mass production of UO2 porous pellets; we believe these results will have immense practical interest.